ISOLASI ENZIM SELULASE DARI PANKREAS KEONG MAS - Siregar, Sri Hilma (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2011)
Extract the cellulose was prepared by the precipitation method using aceton 50% (v/v) and its protein content was analized by Biuret method. The sugar content as the result of the hydrolization of cellulose was determined by Nelson Somogyi method. After precipitation of the protein enzyme, centrifugation and freeze drying were applied and the specific activity of he enzyme cellulose extract was 0.1012 U/mg protein in optimal condition of pH 4.5 and temperature 45oC, where as the maximum velocity 32.94 Î¼g/ml/min and KM value were 0.7279 mg/ml. Respectively the purification fold was 3.58 times and the % recovery was 52.95%.